Peraturan Perpajakan PP Nomor 23 Tahun 2018 sebagai Suntikan Hormon bagi Pelaku UMKM (?) - Ismayantika Dyah Puspasari; Zulistiani, Zulistiani (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
The purpose of this study is to analyze the positive impact of the issuance of Government Regulation no. 23 of 2018 on the growth of MSMEs in terms of capital, profits, and business value. The research method uses a qualitative phenomenological Tran-sendental approach to the concept of "I" with the affirmation of the existence of "I" distinguish one UMKM from another UMKM in seeing the impact of reducing tax rates. The results of this study are that both informants explicitly stated they felt supported by the government with a reduction in the {noema} tax rate so that for them it provided more benefits.